Impact of Social Cultural Factors on Teenage Pregnancies in Ikumba Sub-County Rubanda District. - Ndyamuhakyi, Sonia (Kabale University, 2024)
The study was about the effect of social-cultural factors in promoting teenage pregnancies in the Ikumba sub-county Rubanda district and was guided by the following study objectives; to find out the social-cultural factors contributing to teenage pregnancies in Ikumba Sub-County, to analyse the impact of these social-cultural factors on adolescent sexual behavior and reproductive health outcomes and to suggest the strategies in place for addressing social-cultural influences and teenage pregnancies in Ikumba Sub-County. The researcher used the descriptive research design as appropriate for the study because the study was concerned with finding answers to questions about the research topic under study by the researcher. The Population of this study comprised parents, guardians, and Teenage girls who were added up to get 120 because they are the basis of the study and this provided the relevant answers to the study questions. The sample size is an important feature of any empirical study in which the goal is to make inferences about a population from a sample. For this to be achieved, the researcher used 92 respondents using Krejcie and Morgan's table 1970. Descriptive analysis was used to determine the proportions and frequency of the variables. The results were presented in the form of frequency tables and percentages. The respondents revealed that in Uganda, societal norms often dictate conservative views on sexuality. They revealed that many communities hold traditional beliefs that discourage open discussions about sexual health and reproductive rights. This lack of communication can lead to misinformation among teenagers regarding safe sex practices and contraception as represented by 26% of the respondents. The study recommends launching campaigns that educate both parents and teenagers about the importance of sexual health education. This should include information on contraception, reproductive rights, and the consequences of early pregnancies. The study recommends Collaborating with local leaders and elders who hold significant influence in the community to promote positive attitudes toward adolescent sexual health. Their involvement can help change cultural perceptions that may contribute to teenage pregnancies.